Analisis Penggunaan QRIS untuk Optimalisasi Pendapatan UMKM Desa Sirna Baya Kabupaten Karawang - Suherman, Ujang; Ery Rosmawati; Rengga Pratama (PENG: Jurnal Ekonomi dan Manajemen, 2026)
The development of Micro, Small, and Medium Enterprises  (MSMEs) in Karawang  Regency is  a priority for  the  Karawang  Regency  Government.  The  empowerment  of  MSMEs  is  being  pursued through  the  Cooperatives  Office,  employing  various  empowerment  strategies.  For  example,  in Sirnabaya Village, a village in Teluk Jambe District, Karawang Regency, with a very high population density and a large influx of migrants due to its strategic location close to industrial areas and the city center, it is a potential area for MSME growth and development. However, MSMEs in the area still lack knowledge and use of QRIS as a payment method, even though cashless payment methods are currently trending and popular. To optimize MSME profits in line with technological developments, a research project entitled "Analysis of QRIS Use to Optimize MSME Revenue in Sirna Baya Village, Karawang Regency" was deemed necessary. The purpose of this research was to analyze the effectiveness of cashless payment methods among MSMEs in Karawang Regency. The research method used in this research was qualitative. The results of this study were the MSME community's understanding of the benefits and use of QRIS in transactions.